Synthesis and antiproliferative activity of derivatives of the phyllanthusmin class of arylnaphthalene lignan lactones. Issue 9 (15th May 2018) - Woodard, John L.; Huntsman, Andrew C.; Patel, Pratiq A.; Chai, Hee-Byung; Kanagasabai, Ragu; Karmahapatra, Soumendrakrishna; Young, Alexandria N.; Ren, Yulin; Cole, Malcolm S.; Herrera, Denisse; Yalowich, Jack C.; Kinghorn, A. Douglas; et al.
Graphical abstract: Abstract: A series of arylnaphthalene lignan lactones based on the structure of the phyllanthusmins, a class of potent natural products possessing diphyllin as the aglycone, has been synthesized and screened for activity against multiple cancer cell lines. SAR exploration was performed on both the carbohydrate and lactone moieties of this structural class. These studies have revealed the importance of functionalization of the carbohydrate hydroxy groups with both acetylated and methylated analogues showing increased potency relative to those with unsubstituted sugar moieties. In addition, the requirement for the presence and position of the C-ring lactone has been demonstrated through reduction and selective re-oxidation of the lactone ring. The most potent compound in this study displayed an IC50 value of 18 nM in an HT-29 assay with several others ranging from 50 to 200 nM. In an effort to elucidate their potential mechanism(s) of action, the DNA topoisomerase IIa inhibitory activity of the most potent compounds was examined based on previous reports of structurally similar compounds, but does not appear to contribute significantly to their antiproliferative effects.